PELATIHAN STATISTIK DENGAN MENGGUNAKAN SPSS (STATISTICAL PRODUCT AND SERVICE SOLUTION) UNTUK PENINGKATAN KETERAMPILAN DALAM MENYELESAIKAN TUGAS AKHIR MAHASISWA SEKOLAH TINGGI ILMU EKONOMI WIYATAMANDALA - Shandy Puspita; Andres Dharma Nurhalim; Vivi Adeyani Tandean (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The problem faced by final year students at the Wiyatamandala College of Economics is the lack of practice in producing scientific work. Students' lack of knowledge in making scientific work is due to a lack of understanding of research methodology and mastery of the SPSS application which can help process research data using statistical techniques, even though making research is very important to fulfill students' obligations as a graduation requirement in obtaining a bachelor's degree. The result of this service is that participants understand the concept of SPSS processing with simple research examples used as material for training in analyzing research data using the SPSS application so that students can read and analyze the output results from using the SPSS application